Gut microbial composition and functionality of school-age Mexican population with metabolic syndrome and type-2 diabetes mellitus using shotgun metagenomic sequencing - Carrizales-Sánchez, Ana K.; Tamez-Rivera, Oscar; García-Gamboa, Ricardo; García-Cayuela, Tomás; Rodríguez-Gutiérrez, Nora A; Elizondo-Montemayor, Leticia; García-Rivas, Gerardo; Pacheco, Adriana; Hernández-Brenes, Carmen; Senés-Guerrero, Carolina (Frontiers in Pediatrics, 2023)
Gut metagenome in pediatric subjects with metabolic syndrome (MetS) and type-2 diabetes mellitus (T2DM) has been poorly studied, despite an alarming worldwide increase in the prevalence and incidence of obesity and MetS within this population. The objective of this study was to characterize the gut microbiome taxonomic composition of Mexican pediatric subjects with MetS and T2DM using shotgun metagenomics and analyze the potential relationship with metabolic changes and proinflammatory effects. Paired-end reads of fecal DNA samples were obtained through the Illumina HiSeq X Platform. Statistical analyses and correlational studies were conducted using gut microbiome data and metadata from all individuals. Gut microbial dysbiosis was observed in MetS and T2DM children compared to healthy subjects, which was characterized by an increase in facultative anaerobes (i.e., enteric and lactic acid bacteria) and a decreased in strict anaerobes (i.e., Erysipelatoclostridium, Shaalia, and Actinomyces genera). This may cause a loss of gut hypoxic environment, increased gut microbial nitrogen metabolism, and higher production of pathogen-associated molecular patterns. These metabolic changes may trigger the activation of proinflammatory activity and impair the host’s intermediate metabolism, leading to a possible progression of the characteristic risk factors of MetS and T2DM, such as insulin resistance, dyslipidemia, and an increased abdominal circumference. Furthermore, specific viruses (Jiaodavirus genus and Inoviridae family) showed positive correlations with proinflammatory cytokines involved in these metabolic diseases. This study provides novel evidence for the characterization of MetS and T2DM pediatric subjects in which the whole gut microbial composition has been characterized. Additionally, it describes specific gut microbial microorganisms with functional changes that may influence the onset of relevant health risk factors.